An Esrrb and Nanog Cell Fate Regulatory Module Controlled by Feed Forward Loop Interactions - Sevilla, Ana; Papatsenko, Dimitri; Mazloom, Amin R.; Xu, Huilei; Vasileva, Ana; Unwin, Richard D.; LeRoy, Gary; Chen, Edward Y.; Garrett-Bakelman, Francine E.; Lee, Dung-Fang; Trinite, Benjamin; Webb, Ryan L.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cell fate decisions during development are governed by multi-factorial regulatory mechanisms including chromatin remodelling, DNA methylation, binding of transcription factors to specific loci, RNA transcription and protein synthesis. However, the mechanisms by which such regulatory “dimensions” coordinate cell fate decisions are currently poorly understood. Here we quantified the multi-dimensional molecular changes that occur in mouse embryonic stem cells (mESCs) upon depletion of Estrogen related receptor beta (Esrrb), a key pluripotency regulator. Comparative analyses of expression changes subsequent to depletion of Esrrb or Nanog, indicated that a system of interlocked feed-forward loops involving both factors, plays a central part in regulating the timing of mESC fate decisions. Taken together, our meta-analyses support a hierarchical model in which pluripotency is maintained by an Oct4-Sox2 regulatory module, while the timing of differentiation is regulated by a Nanog-Esrrb.